Testing for the Lucas Critique: A Quantitative Investigation - Jesper Lindé (Sveriges Riksbank, 2000)
In this paper, I try to shed some new light on the puzzle why the Lucas critique, belived to be important by most economists, seems to have received very little empirical support. I use a real business cycle model to examine the properties of the super exogeneity test, which is used to detect the applicability of the Lucas critique in practice. The results suggest that the super exogeneity test is not capable of detecting the relevance of Lucas critique in practice in small samples.
Keywords: C22; C52; E41; 330; Lucas critique; Real business cycle model; Super exogeneity test; Taylor rules; Money demand; Consumption function